Budidaya Kepiting Bakau Menggunakan Vertical Crab House pada UMKM Aneka Jaya, Kelurahan Lalolang, Kecamatan Tanete Rilau, Kabupaten Barru - Marsuki, Marsuki; Zulhayyir, Zulhayyir; Lukman, Sri Hardiyanti (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This study aims to analyze the application of Vertical Crab House (VCH) technology in mud crab cultivation at Aneka Jaya MSME, located in Lalolang Village, Tanete Rilau Subdistrict, Barru Regency. The research employed a descriptive qualitative approach through field observation, interviews, and documentation. VCH is an innovative vertical farming system that enables higher crab stocking density in limited space, improved feed efficiency, and better water quality management. The results indicate that the adoption of VCH increased crab survival rates up to 80%, reduced feed usage by 20%, and simplified maintenance. Economically, the MSME experienced a 25% increase in income per harvest cycle. Furthermore, this technology enhanced the entrepreneurs’ awareness of sustainable and environmentally friendly aquaculture practices. These findings are expected to serve as a reference for developing crab farming technology at the MSME scale.